Negotiating Service Activism in China: The Impact of NGOs' Institutional Embeddedness in the Local State. Issue 111 (4th May 2018) - Yuen, Samson
Abstract: The rise of government procurement has transformed the associational landscape in China. In many localities, local states have launched procurement programs to collaborate with NGOs, which in turn provide social services to community residents. While it has been argued that government funding shapes NGOs into compliant service providers, this article contends that state-funded NGOs are able to engage in advocacy through service delivery, a strategy known as 'service activism'. By examining three NGOs in Guangdong Province, this article argues that NGOs' success in service activism is determined by their degree of institutional embeddedness in the local state and the nature of their advocacy strategies. While both strongly or weakly embedded relationships can weaken the impact of advocacy, progressive strategies in sensitive issue areas can weaken collaboration and draw repression.